Investigation of The Effect of Different Activators on Borosintering Process - Ertürk, Lutuf; Selçuk, Burhan (Journal of Novel Engineering Science and Technology, 2024)
In parts produced by the P/M method, boriding is generally applied as a separate process after sintering. If the package boriding process is carried out during the sintering of the powder compact, sintering and boriding can be integrated; This not only prevents parts from deforming due to secondary heating, but can also reduce energy consumption. Carrying out sintering and boriding processes simultaneously is called Borosintering (B/S). Studies in the literature have stated that various material properties are improved thanks to the boride layers formed as a result of the borosintering process. It has been observed that the effect of different boronizing environments on the borosintering process has not been examined in any of the studies. In this study, media containing different weight ratios of silicon carbide (75%, 85%, 90%), boron carbide (5%, 10%, 20%) and the remainder one of various activators (Na2CO3, NaCl, Na2B4O7 (anhydrous borax) and NaF) in the boronizing medium were tested. Wear test (0.6 m/s sliding speed, 52 N load, 500 m distance, counter: 16MnCr5) was applied to some selected samples, the boride layer was examined by SEM, and elemental analysis was performed by EDX. Phases in the boride layer were detected by XRD. The hardness of the layer was measured with a microvickers test machine. The study showed that many different activators can be used in the borosintering process and that activators have a significant effect on the specifications of the boride layer. It was concluded that the NaF activator accelerates the formation of the boride layer more than other activators and creates a boride layer with better properties.